MEMBANGUN LOYALITAS PELANGGAN MELALUI KEPUASAN YANG DIPENGARUHI OLEH KUALITAS PRODUK, PERSEPSI HARGA DAN CITRA MEREK (Studi Pada Produk Smartphone Merek Oppo) - Putu Sundari Aprelia Dewi; Ni Wayan Sri Suprapti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2018)
The purpose of this study is to determine the effect of satisfaction in building customer loyalty influenced by the product quality, brand image and price perception. The study was conducted in Denpasar City, involving 105 respondents. Respondents were selected using purposive sampling. The criteria od respondent involved is they have purchased an Oppo smartphone. The research instrument used a questionnaire. The data collection is conducted by distributing questionnaires which is tested using the validity test and reliability test to determine the accuracy and consistency of the questionnaire. Furthermore, data collected from the questionnaires are analyzed using path analysis (Path Analysis). The results are found that customer satisfaction has a positive and significant impact on customer loyalty and brand image is the most variable that affect the customer satisfaction